Cooperative Learning: Theories, Principles, and Techniques - Yanuar Dwi Prastyo; Feranita Dice Sansisca (International Conference on Education and Language (ICEL), 2013)
This paper discusses the uses of Cooperative Learning (CL) in the foreign language classroom. Some definitions of cooperative learning are discussed in the first part of the paper. Some other key areas discussed in the paper are: a. some principles of cooperative learning, b. techniques of cooperative learning that we can apply in our foreign language classroom.